Fatwa on the Marriage of a Person Who Has a Deviation of Sexual Orientation in Islamweb.net from the Perspective of Maqāṣid al-Sharī'ah - Aisyah, Nabilah Rohadatul; Tussa’banniya, Nabila; Abida, Rossana Farah; Musyafa’ah, Nur Lailatul (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2025)
Nowadays, more and more people have a deviant sexual orientation. The laws of their marriage, both same-sex and of different sexes, have caused legal debate among clerics, including on websites. This study aims to examine the fatwa of islamweb.net scholars on marriage for someone who has a deviant sexual orientation. This research is a normative legal research with a conceptual approach. Primary data is collected through the fatwa of islamweb.net clerics, while secondary data comes from books and scientific articles. The collected data was analyzed descriptively with the theory of Maqāṣid al-sharī'ah. The results of the study show that islamweb.net clerics view homosexuality as a form of deviance that needs to be cured through spiritual and medical approaches, with heterosexual marriage as